Evaluation of the hadrochemical properties of wells water in northern Ali Al-Gharbi district - Mahdi, Rafid (Al-Adab Journal, 2023)
Groundwater is important in all geographical regions, especially the dry ones, because it is an alternative source in reducing dependence on available surface water, but characteristics of groundwater vary according to its sources or reservoir, rocks that surround it and human pollutants. This study showed that groundwater (pH) is within the Iraqi standard specifications, while (EC), (TDS) and (T.H) are higher than the allowed specifications to be used for drinking, heavy metal pollutants Lead (Pb) is higher than the permissible levels and (Ni, Cd, Mn) all samples are free of Nickel, Cadmium and Manganese. Water quality index (WQI) for Wells (3-5-8) is excellent water, wells (11-13-15) are characterized with poor water, while the rest of wells are characterized having a good drinking water, for agricultural use Sodium percentage indicator all wells within the acceptable category except for (9-11) are within the good classification, the sodium adsorption ratio indicator for wells (5-9-10-14) are within the good category and wells (11-13-15) are within the category unsuitable class while the rest are in the inferior class, index of residual sodium carbonate all wells are within the good class, Permeability Index all wells are within the appropriate class for agricultural irrigation.